Fusing Electricity and Carbon Markets in the American West: Can Organized Electricity Markets Bolster Cap-and- Trade? - Caulkins, Luther (Columbia Journal of Environmental Law, 2022)
Efforts to “link” together several state or provincial GHG cap-and- trade programs to form a regional cap-and-trade initiative in western North America began in the early 2000s but never realized their aims. Now, emerging organized electricity markets in western states, includ- ing the Energy Imbalance Market, offer the possibility of integrating these markets with a regional cap-and-trade program to cut emissions at a low cost. This Note explains how a regional cap-and-trade program could be incorporated into the West’s nascent organized electricity mar- kets. It then argues that doing so could cost-effectively reduce power sector emissions, guide clean energy development, and alleviate incon- sistencies between varying state climate regulations. However, because of a phenomenon called “resource shuffling,” these benefits would not materialize unless all or most western states participate in the cap-and- trade program. To realize the climate benefits of integrating organized markets with cap-and-trade, climate-concerned advocates and policy- makers should therefore continue to aspire to a national cap-and-trade program or a regional program that attracts broad participation.